The Influence of an External Magnetic Field on Multi-photon Non-linear Absorption Coefficient of a Strong Electromagnetic Wave in Two-dimensional Graphene - Tuan, Tran Anh; Vi Ba, Cao Thi; Dinh Nam, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1, 2024)
Based on the quantum kinetic equation for electrons, we theoretically studied the Quantum Multi-photon Nonlinear Absorption of a Strong Electromagnetic Wave (EMW) in two-dimensional graphene with electron-optical phonon scattering mechanism. The general multi-photon absorption coefficient was presented as a function of the temperature, the external magnetic field, the photon energy, and the amplitude of external EMW. The results show that in the presence of the magnetic field, absorption spectral lines appear consistent with the magneto-phonon resonance conditions. In which, the effect of multi-photon absorption is stronger than that of mono-photon absorption. Besides, the quantum multi-photon nonlinear absorption phenomenon has been studied from low to temperatures. This transcends the limits of the classical Boltzmann kinetic equation which is studied in the high-temperature domain. The computational results show that the dependence of Multi-photon Nonlinear Absorption Coefficient (MNAC) on the above quantities is consistent with the previous theoretical investigation. Another novel feature of this work is that the general analytic expression for MNAC shows the Half Width at Half Maximum (HWHM) dependence on the magnetic field which is in good agreement with the previous experimental observations. Thus, our estimation might give a critical prediction for future experimental observations in graphene.